Pengaruh Promosi Dan Lingkungan Kerja Terhadap Prestasi Kerja Pegawai Kantor Bupati Gorontalo - Meimoon Ibrahim (Universitas Gorontalo, 2018)
Meimoon Ibrahim. This study aims to analyze the effects of promotion and work environment on work achievement with the respondents of Local Government office employee. The research focus is protion and ewoek environment on work achievement with the respondents of 100 employees from 133 employees using proportional random sampling method. The research method used explanatory and the data analysis used multiple linear regression analysis. The research result shows that, promotion and work environment simultaneously provide positive and significant effect on work achievement. Partially, the promotion variable provides positive effect but not significant on work achievement, the work environment variable that becomes the most dominant variable has a positive and significant effect on work achievement, among the four observed variables.